KNOWLEDGE AND PERCEPTION OF MALNUTRITION AND ITS EFFECT ON UNDER-FIVE CHILDREN AMONG MOTHERS ATTENDING PRIMARY HEALTH CENTERS IN SAGAMU LOCAL GOVERNMENT AREA, OGUN STATE: A CROSS-SECTIONAL STUDY - Abaribe, Chidinma; Ayodeji, Jesupemi; Makinde, Scholastica; Onuiri, Amarachi (Student’s Journal of Health Research Africa, 2025)
Background Childhood malnutrition remains a global challenge and the most prevalent nutritional problem in developing countries, including Nigeria. This study assessed the knowledge and perception of malnutrition and its effect on under-five children among mothers attending primary health centers in the Sagamu Local Government Area of Ogun State, Nigeria. Method The study adopted a cross-sectional quantitative design and used a multi-stage sampling technique to select sixty-one mothers from the three selected primary health centers in Sagamu LGA. A researcher-developed questionnaire was used for the collection of data from participants. Data was collected, coded, and analyzed using Statistical Package for the Social Sciences (SPSS) 23. Descriptive and inferential statistics were used to present the findings from the study, and all were tested at the level of 0.05 significance Results The result shows that the majority of the mothers were between the ages of 18 and 28 years (44.9%), attained tertiary education (73.5%), were from Yoruba land (65.3%), were Christian (75.5%), and most had one to three children (80.6%). Mothers had high knowledge of malnutrition 138(91.8%), and high knowledge of the effects of malnutrition 144 (95.8%). The result also revealed a significant relationship between respondent’s knowledge of malnutrition and the effects of malnutrition (p= 0.001), level of education and knowledge of malnutrition (p= 0.000), and between the knowledge of malnutrition and perception of malnutrition in under-five children (p= 0.006) Conclusion The study concludes that the Majority of the mothers demonstrated high knowledge of malnutrition and good knowledge of its effects, and it established a positive relationship between knowledge and perception of malnutrition in children under five. Recommendation Therefore, the study recommended that training programs should be done periodically for mothers to ensure they are abreast with the proper knowledge and ways to prevent malnutrition in their under-five children.